Mass spectrometric analysis of cell metabolism following parasitic infection - Anschütz, Nils Holger; Justus Liebig University Giessen (My University, 2023)
Neospora caninum and Cryptosporidium parvum belong to the phylum Alveolata (Subphylum Apicomplexa) are two very widespread parasites. Cryptosporidiosis, caused by C. parvum, is a zoonosis. This is not the case with neosporosis, which is caused by N. caninum. However, there is growing concern that N. caninum may eventually become a threat to humans, as clinically manifest neosporosis has also been reported in two rhesus monkeys. Affecting more than 1 billion people worldwide, human cryptosporidiosis remains a neglected poverty-related disease (PRD) that can be fatal in already weakened patients, especially young children. N. caninum has a significant economic impact on the livestock industry as it is a major cause of reproductive disorders not only in cattle but also in other small ruminant species. The spread of both parasites and associated diseases is increasing due to climate change and the global movement of people and transport of goods. Both parasites have a demonstrable negative impact on people's quality of life and should therefore be the focus of scientific research. But there is still a lot of catching up to do, especially in the area of basic research in regard to the biomolecular composition of the two parasites and their influence on the metabolism of their hosts. This deficiency could be counteracted in this work. The parasites were studied using matrix-assisted laser desorption/ionisation (MALDI) mass spectrometry (MS) combined with high performance liquid chromatography (HPLC). MALDI was used as MS and MS imaging (MSI) method. The MALDI experiments were performed using the SMALDI (scanning microprobe matrix-assisted laser desorption/ionisation) ion source, which operates at atmospheric pressure. It is suitable for the analysis of complex 3D surfaces with a low sample amount requirement. MS instrumentation has improved considerably over recent years, allowing detailed mass analysis to determine compounds from their very precise molecular masses. It is possible to annotate and subsequently identify analytes. For the structural verification of the markers, HPLC-MS/MS experiments were combined with database search. Identifying molecular biomarkers of parasite-infected host cells and further elucidating their functions were among the main objectives of this study. The statistically relevant biomarkers, with the focus on lipids, that were found by MS, annotated by database and identified by HPLC-MS/MS measurements, were also found and visualized with AP-SMALDI MSI in infected monolayers and host tissue. There is an overlap of the identified markers between N. caninum and C. parvum as well as between the two parasites and other parasites from the literature. PI (36:1) has been identified as a marker of host cell infection by N. caninum, C. parvum, T. gondii and B. besnoiti. Phosphatidylinositol is found in cell membranes and is essential for anchoring proteins to the membrane. They play a role in the transition of the parasite (T. gondii) between its stages (tachyzoites and bradyzoites). Overall, the present approach provides new metabolic insights into both diseases that have been neglected by science.
Keywords: mass spectrometry; msi; parasite; lipid; ddc:540